Bibliometrik Analysis: Signal Preprocessing Techniques for Kualitas Sinyal Electrogram - Odi Nurdiawan; Dadang Sudrajat; Fathurrohman; Ade Rizki Rinaldi (Ikatan Ahli Informatika Indonesia, 2024)
This study explores electroencephalogram (EEG) signal preprocessing techniques used in the early detection and diagnosis of epilepsy, aiming to enhance the quality and reliability of data used in clinical applications. Effective signal preprocessing techniques are crucial for minimizing artifacts and noise, which can obscure critical information in EEG signals. More accurate EEG signal processing allows for the identification of abnormal patterns associated with various neurological conditions, such as epilepsy, which heavily relies on this signal analysis for precise diagnosis. This study conducted a bibliometric analysis using a descriptive approach to identify research trends, geographic distribution, institutional contributions, and key authors in this field. Data was collected from the Scopus database using the keywords